The training and expectations of medical students in Mozambique - Gonçalves Luzia; Adam Yussuf; Schwalbach João; Sousa Fernando; Ferrinho Paulo (BMC, 2007)
Abstract Background This paper describes the socio-economic profile of medical students in the 1998/99 academic year at the Universidade Eduardo Mondlane (UEM) Medical Faculty in Maputo. It aims to identify their social and geographical origins in addition to their expectations and difficulties regarding their education and professional future. Methods The data were collected through a questionnaire administered to all medical students at the faculty. Results Although most medical students were from outside Maputo City and Maputo Province, expectations of getting into medical school were already associated with a migration from the periphery to the capital city, even before entering medical education. This lays the basis for the concentration of physicians in the capital city once their term of compulsory rural employment as junior doctors is completed. The decision to become a doctor was taken at an early age. Close relatives, or family friends seem to have been an especially important variable in encouraging, reinforcing and promoting the desire to be a doctor. The academic performance of medical students was dismal. This seems to be related to several difficulties such as lack of library facilities, inadequate financial support, as well as poor high school preparation. Only one fifth of the students reported receiving financial support from the Mozambican government to subsidize their medical studies. Conclusion Medical students seem to know that they will be needed in the public sector, and that this represents an opportunity to contribute to the public's welfare. Nevertheless, their expectations are, already as medical students, to combine their public sector practice with private medical work in order to improve their earnings.